Homework 3 Feb
Homework 3 Feb
Homework 3 Feb
Divergence of a product: Given that is a scalar field and a vector field, show that
div() = (grad) + div
grad() = ( ),
= , + ,
= (grad ) + grad
Now, div() = tr(grad()). Taking the trace of the above, we have:
div() = (grad ) + div
= , + ,
= , + , = curl curl
5. Given a scalar point function and a vector field , show that curl () =
curl + (grad ) .
curl () = ( ),
= (, + , )
= , + ,
= () + curl
= (grad ) + (div )
7. For a scalar field and a tensor field show that grad () = grad +
grad. Also show that div () = div + grad
grad() = ( ),
= (, + , )
= grad + grad
Furthermore, we can contract the last two bases and obtain,
div() = (, + , )( )
= (, + , )
= , + ,
= grad + div
= ( , + , )
= ( , + , )
= ( )grad + ( )grad
9. For a vector field , show that grad( ) is a third ranked tensor. Hence or
otherwise show that div( ) = curl .
The secondorder tensor ( ) is defined as . Taking the covariant
derivative with an independent base, we have
grad( ) = ,
This gives a third order tensor as we have seen. Contracting on the last two bases,
div( ) = ,
= ,
= ,
= curl
10.
grad = ( ),
The divergence of this third order tensor is the contraction of the last two bases:
div () = tr(grad ) = ( ), ( ) = ( ),
= ,
= , = , = grad
11.
12.
so that
curl ( ) = ,
= ( ) ,
= , ,
= (div ) grad
13.
14.
Given a scalar point function and a vector field , show that curl () =
curl + () .
curl () = ( ),
= (, + , )
= , + ,
= () + curl
15.
16.
17.
18.
19.
Given that and are scalar fields, show that div (grad grad ) = 0
grad grad = , ,
= , , + , ,
= , , + , ,
= , , + , , = 0
Each term vanishing on account of the contraction of a symmetric tensor with an
antisymmetric.
20.
21.
Show that =
Note that
= |
= |
| = |
= |
| |
| + |
|
= |
| |
| + 3 |
|
= |
| =
22.
2 :
Now,
(2 ) = 2
=
: + :
= 2:
= :
=
:
|()|
as required.
Given a tensor field , obtain the vector T and show that its divergence
is : () + div
23.
24.
25.
curl ( ) = ( ), = ( , + , )
= , + ,
= ( ) ( , ) + ( , ) ( )
= ( )( , ) + ( , ) ( )
= ( )(grad ) + (curl ) = [(grad ) ] + (curl )
upon noting that the vector cross is a skew tensor.
26.
= ( ) ( ),
= ( ) ( , + , )
= [ , + , ( , + , )]
= [( ), ( ), ]
= div( )
since div( ) = ( ), ( ) = ( ), .
27.
Given a scalar point function and a second-order tensor field , show that
curl () = curl + (() ) T where [() ] is the skew tensor
,
curl () ( ),
= (, + , )
= , + ,
= ( , ) ( ) + ,
= curl + (() ) T
28.
curl , = .
The gradient of is .
, = ,
Clearly,
div(curl ) = , = ,
= , = curl(div T )
29.
2 ( ) = 2 + 2 .
By definition, 2 ( ) = ( ), . Expanding, we have
( ), = ( , + , ), = ( + , )
= ( , + , , + , )
= ( , + , + , )
= , + , + ,
When the coordinates are orthogonal, this becomes,
2
+ 2
2
( )
where we have suspended the summation rule and is the square root of the
appropriate metric tensor component.
30.
= [ ( , + , )]
= ( + ), = 2 , = 2
= 6
31.
Given the contravariant vector and with their associated vectors and ,
the contravariant component of the above cross product is .The
required divergence is simply the contraction of the covariant derivative of this
quantity:
( ), = , + ,
where we have treated the tensor as a constant under the covariant
derivative.
Cyclically rearranging the RHS we obtain,
( ), = , + , = , + ,
where we have used the anti-symmetric property of the tensor . The last
expression shows clearly that
div = curl curl
as required.
32.
+ ( )
= [ . , .. , ]( ) + [
.. , . , ]( )
+ [ .. , .
. , ]( )
33.
= , = ,
which obviously vanishes on account of the symmetry and antisymmetry in and
. In this case,
curl(curl )
= [2 (tr ) div(div )] grad(grad (tr)) + 2(grad(div ))
2
T
For a scalar function and a vector show that the divergence of the vector
is equal to, +
34.
( ), = , + ,i
Hence the result.
35.
Taking the associated (covariant) vector of the expression for the cross product in
the last example, it is straightforward to see that the LHS in indicial notation is,
( ),
Expanding in the usual way, noting the relation between the alternating tensors
and the Kronecker deltas,
( )
( ,
=
( , , )
, ) = |
| ( , , )
= ( )( , , )
=
= , , + , ,
= , , + , ,
Which is the result we seek in indicial notation.
36.
, = and div () = .
() =
, =
( )
1
=
=
[ + ] = .
( )
(
)=
( )=
1
=
( )3
1
3 ( )2 2
( ) , =
=
= .
( )3 ( )3
() , =
=
( )2
( )2
( ) = so that
1 1
, =
=
= 2 = 3
Consequently,
( 2 )) +
( 3 )
3 (
(, ) =
( )=
3
6
( 3 )
3
( ) + (
) 3 + (3 2 )
3
=
=
= 3 + 5
6
6
3 3 3 2
, = 3 + 5 = 3 + 5 = 0.
1
1
3
1
div ( ) = ( ) , = , + ( ) = + ( ( )
)
,
3
1
3 3 1 2
= + [ ( 2 ) ] = 3 = =
, =
37.
= ( ) ( )
= ( ) + ( )
= [ ( ) ( ) ]
38.
39.
= [
] ( )
= ( ) ( ) = ( )
40.
The position vector in the above example = . Show that (a) div = , (b)
div ( ) = , (c) div = 3, and (d) grad = and (e) curl ( ) =
grad = ,
= =
div = ,
= = = 3. = = grad( )
= ( ), = ( , + , )
= ( + ) = ( + )
= 4 = 4
curl( ) = ( ),
= ( , + , )
= ( + )
= + = =
41.
||
= ||
: = lim
( + )
0
||
| + |
: = lim
0
| + | = tr( + )( + )T = tr(T + T + T + 2 T )
Note that everything under the root sign here is scalar and that the trace
operation is linear. Consequently, we can write,
tr (T ) + tr ( T ) + 2tr ( T )
2:
| + | = lim
lim
=
0
0 2tr(T + T + T + 2 T )
2:
=
:
||
So that,
||
: =
:
||
or,
||
=
||
42.
Show that
3 ()
det()
= the cofactor of .
= [
+
+
]
3!
= [ + + ]
3!
1
= [ + + ]
3!
1
= [ c ]
2!
Which is the cofactor of [ ] or
43.
() = det() tr( )
det
1 2 3
(
)
det =
( ) = (1 2 3 + 1 2 3 + 1 2 3 )
= (1 2 3 + 1 2 3 + 1 2 3 )
= [(11 1 + 12 2 + 13 3 ) 2 3 + 1 ( 12 1 + 22 2
+ 23 3 ) 3 + 1 2 ( 13 1 + 32 2 + 33 3 )]
All the boxed terms in the above equation vanish on account of the contraction of
a symmetric tensor with an antisymmetric one.
(For example, the first boxed term yields, 12 2 2 3
Which is symmetric as well as antisymmetric in and . It therefore vanishes. The
same is true for all other such terms.)
det() = [(11 1 )2 3 + 1 (22 2 )3 + 1 2 (33 3 )]
1 2 3
=
= tr( 1 ) det()
as required.
44.
Without breaking down into components, establish the fact that det()
=
(det()) = [ (det())]: ( )
(det()) = [det() ] =
45.
det()
1
1
=
=
det()
det()
det()
=
46.
det( 1 )
1
1
=
( 2 )
1
det( )
1
=
det( 1 ) ( 2 )
1
det( )
=
47.
= A S = A S
tr() =
tr()
S
A S
=
S
=
as required.
T
( : )
= A = =
48.
tr( T ) = ( T ) = T
49.
T T)
(
tr =
tr[( T )T ] = [( T )T ] = T
50.
Let be a symmetric and positive definite tensor and let 1 (), 2 ()and3 ()
1 ()
= 1 () and (c)
3 ()
1 ()
= 3 () 1
1 () 1 ()
=
=
=
which is the identity tensor as expected.
2 ()
=
[
where we have utilized the fact that 2 () = 2 [tr 2 () tr( 2 )]. Consequently,
2 () 1
=
[
= [ + ]
2
1
= [ + ] = ( )
2
= 1 ()
1
det() || =
3!
Differentiating wrt , we obtain,
= [
+
+
]
3!
= [ + + ]
3!
1
= [ + + ]
3!
1
= [ c ]
2!
Which is the cofactor of [ ] or
51.
Taking the trace of both sides and noting that both trace and the integral are
linear operations, therefore we have,
(div ) = tr(grad )
= tr( )
52.
becomes,(grad ) =
Recall that for a vector field, that for a vector field
(div ) =
, = ,
= , = grad
For the arbitrary constant vector , we therefore have that,
(div[]) = grad =
grad =
53.
= curl
= curl
= (grad ): ( )
As required.
54.
= [(div ) (grad ) ]
= (curl )
= ( ), ( )
= ( , + , )( )
= ( , + , )( )
= ( , + , )
= [(grad ) + ( curl )]
As required.
To establish the second result, we allow = = . As before, we
have that,
(curl )T = , ( )
= ( ), ( )
= ( ) , ( )
= , ,
= [(div ) (grad ) ]
Because (grad )T = , ( ) = , .